Peranan Self Efficacy dan Self Regulated Learning Terhadap Prestasi Akademik Mahasiswa: (The Role of Self Efficacy and Self Regulated Learning on Student Academic Achievement) - Anisa Anisa; Nurul Magfirah; Rahmatia Thahir (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2021)
This research is an ex post facto type. Aim to: analyze the effect of self-regulated learning and self-efficacy on the academic achievement of students of the Biology Education Study Program, Muhammadiyah University of Makassar. The population in this study were all students of the Biology Education Study Program, Muhammadiyah University of Makassar. The research sample of 46 students was obtained using purposive sampling technique. The variables studied consisted of two independent variables, namely self-efficacy (x1) and self-regulated learning (x2) and one dependent variable, namely academic achievement (y). Data collection techniques through questionnaires to obtain self-regulated learning and self-efficacy data, for academic achievement data obtained through documentation techniques. The results of data analysis indicate that the correlation between self-efficacy and self-regulated learning and academic achievement has a very strong relationship. It can be concluded that self efficacy and self regulated learning play an important role in student academic achievement. Students who have high self-efficacy and self-regulated learning will be able to adapt well to academic activities in fairly dense tertiary institutions. So that it will help students to achieve brilliant academic achievements. Abstrak. Mahasiswa secara mandiri memantau perkembangan kegiatan akademiknya, seperti nilai-nilai dari mata kuliah dan tugas yang diberikan. Mahasiswa yang mampu beradaptasi secara cepat dengan proses pembelajaran di perguruan tinggi tentu akan dapat menjalani aktivitas akademik yang cukup padat dengan baik. Untuk itu mahasiswa perlu memiliki self regulated learning dan self efficacy yang baik. Oleh karena itu penelitian ini bertujuan untuk menganalisis pengaruh self regulated learning dan self efficacy terhadap prestasi akademik mahasiswa Prodi Pendidikan Biologi Universitas Muhammadiyah Makassar. Penelitian ini berjenis ex post facto. Populasi dalam penelitian ini adalah seluruh mahasiswa Prodi Pendidikan Biologi Universitas Muhammadiyah Makassar. Teknik pengumpulan data menggunakan kuesioner. Teknik analisis data menggunakan uji regresi linear berganda. Hasil analisis data yang menunjukkan bahwa korelasi antara self efficacy dan self regulated learning dengan prestasi akademik memiliki hubungan yang sangat kuat. Dapat disimpulkan bahwa self efficacy dan self regulated learning berperan penting terhadap prestasi akademik mahasiswa. Mahasiswa yang memiliki self efficacy dan self regulated learning yang tinggi akan mampu beradaptasi dengan baik dalam kegiatan akademik di perguruan tinggi yang cukup padat. Sehingga hal tersebut akan membantu mahasiswa untuk meraih prestasi akademik yang gemilang.